Analysis of local dairy value chain for smallholder pastoralists in Simanjiro District, Tanzania - Sumuni, Catholic (Mzumbe University, 2024)
A Dissertation Submitted in Partial/Fulfillment of the Requirements for the Master’s Degree of Science in Procurement and Supply Chain Management of Mzumbe University 2013